Biography driven instruction for English language learners from China: a qualitative case study - Wang, Jinhua (Kansas State University, 2021)
The purpose of this qualitative case study was to explore the English language learning experiences of three international students from China who studied or are currently studying at a Midwest state institution and have been exposed to GTM in China and BDI in the United States. This multiple case study was conducted with purposeful and criterion-based sampling. Symbolic interactionism was the methodological lens I chose for this study. Biography-Driven Instruction framework was the theoretical lens. The participants’ narratives were organized using a first-person vignette to interpret their experiences with both GTM and BDI. A first-person view poem was also constructed to represent the data using the participants’ own words of choice. Then I presented a detailed cross-case analysis to unpack the poem and gained some analytical insights by comparing and contrasting the similarities and differences across each participant. Findings indicate that the three participants had to sacrifice their personal motivations, interests and needs to align with family, school and societal expectations, and they were forced to give up individuality to conform to family and school culture. In addition, teachers teaching in tension were revealed in order to accommodate to the societal needs and parents’ pressure as well as push the participants through the rigid assessment system within a Chinese education context. The three participants had to use their sense of self and self-efficacy to navigate these tensions and struggles when they did not personally feel motivated to learn English. The outcomes of this research suggest avenues for policy makers, administrators, EFL teacher educators and professional development organizers to support the integration of BDI approach into the current GTM-dominated EFL classrooms in China. It is necessary for all the involved stakeholders to understand the importance of mitigating the tensions and struggles caused by societal needs, parents’ expectations and academic mandates so they can lead the change process and leverage formal and informal avenues of integrating BDI approach into GTM teaching. These avenues will provide possibilities for Chinese EFL learners to approach new ways of English language learning and fulfill the purpose of real-life communication and meaningful learning, thus helping them foster stronger intercultural awareness and acquire better communicative competence.
Keywords: BDI; EFL; ELL; Motivation; Socio-cultural; SLA